EDUCATION SUPPORT SYSTEM IN THE NEW NORMAL FOR UNDERGRADUATE STUDENTS IN THAILAND NATIONAL SPORTS UNIVERSITY CHIANG MAI CAMPUS - Lertpiriyachaikul, Boonchai; Panyakham, Chokchai (Academic Journal of Thailand National Sports University, 2024)
This research aims to study the conditions, problems and guidelines for developing an educational support system that is important for successful learning in the new lifestyle era. Data were collected from a sample of 302 students of the Thailand National Sports University Chiang Mai Campus. The tool used to collect the data was a questionnaire. Analysis of data by finding percentages, averages, standard deviations, and content analysis can be summarized as follows: The condition of the educational support system for students of the Thailand National Sports University Chiang Mai Campus overall was at a good level. The average was 4.03 when considering the phase. Support during the study and support during the evaluation period was at a good level with an average of between 3.90 – 4.15, the problem is that public relations had little access to the student target. The educational support system for students of Thailand National Sport University Chiang Mai Campus is important for successful learning in the New Normal era. It is divided into 3 phases: Pre-semester support, support during the study and support of the assessment phase, each phase consists of eight sub - support areas.